2002
DOI: 10.1214/aop/1023481004
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations of the free energy in the REM and the $p$-spin SK models

Abstract: We consider the random uctuations of the free energy in the p-spin version of the Sherrington-Kirkpatrick model in the high temperature regime. Using the martingale approach of Comets and Neveu as used in the standard SK model combined with truncation techniques inspired by a r e c e n t paper by T alagrand on the p-spin version, we prove that (for p even) the random corrections to the free energy are on a scale N ;(p;2)=4 only, and after proper rescaling converge to a standard Gaussian random variable. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(126 citation statements)
references
References 27 publications
6
119
1
Order By: Relevance
“…Eisele [8] and Olivieri and Picco [13] have rigorously derived the limit (1.3) (in probability and a.s.) and also extended this result to the case where X i have the Weibull-type tail (1.2) (case B). 1 Recently, a detailed analysis of the limit laws for Z n (β) in the Gaussian case has been accomplished by Bovier et al [6]. In particular, is has been shown that in addition to the phase transition at the critical point β c , manifested as the LLN breakdown for β > β c , within the region β < β c there is a second phase transition atβ c = log 2/2 = 1 2 β c , in that for β >β c the fluctuations of Z n (β) become non-Gaussian.…”
Section: Random Energy Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Eisele [8] and Olivieri and Picco [13] have rigorously derived the limit (1.3) (in probability and a.s.) and also extended this result to the case where X i have the Weibull-type tail (1.2) (case B). 1 Recently, a detailed analysis of the limit laws for Z n (β) in the Gaussian case has been accomplished by Bovier et al [6]. In particular, is has been shown that in addition to the phase transition at the critical point β c , manifested as the LLN breakdown for β > β c , within the region β < β c there is a second phase transition atβ c = log 2/2 = 1 2 β c , in that for β >β c the fluctuations of Z n (β) become non-Gaussian.…”
Section: Random Energy Modelmentioning
confidence: 99%
“…In the present work, we extend these results to the class of distributions with Weibull/Fréchet-type tails of the form (1.2). As compared to the paper [6] which proceeded from extreme value theory, we use methods of theory of summation of independent random variables. This general and powerful approach simplifies the proofs and in particular reveals that non-Gaussian limit laws are in fact stable.…”
Section: Random Energy Modelmentioning
confidence: 99%
“…In the appropriate scaling limit, the appearance of the bias is abrupt and corresponds to a phase transition in variants of the random energy model (REM) [20][21][22][23][24]. The connection between the random energy model and the Jarzynski estimator of free energy differences was first made in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…The point process ͑1.18͒ is the limiting object which appears in the REM. 15 Indeed, in this case t ‫ء‬ ͑0͒ =0, and, hence, ͑0͒ = M͑0͒ = ͱ 2 log 2, which in turn implies that the scaling constants ͑1.15͒ and ͑1.16͒ coincide with that of the REM without external field.…”
Section: ͑117͒mentioning
confidence: 84%